Manajemen Sarana dan Prasarana di MA Darul Iman Tambak Timur Bawean - Syarifuddin, Nur; Ula, Rifatul (PT. Cahya Edupreneur Indonesia, 2023)
This study aims to determine the management of facilities and infrastructure used and describe the process of procuring, maintaining and removing facilities and infrastructure at Madrasah Aliyah Darul Iman Kg. Solo Tambak Timur, Tambak sub-district, this research is case study research that is qualitative in nature, data collection techniques used are observation, interviews and documentation of educational institutions at Madrasah Aliyah Darul Iman, in data analysis techniques this research uses data reduction stages, data presentation and conclusion. planning for facilities and infrastructure is carried out by submitting assistance to the government, procurement of facilities and infrastructure is carried out in accordance with the planning of facilities and infrastructure, use and maintenance of facilities and infrastructure according to the needs of students, inventory according to the provisions of the data every year, deletion of goods is carried out by conditionally based on the condition of the goods, the inhibiting factor for the management of facilities and infrastructure is the lack of funds, while the supporting factor is that the madrasah facilities are adequate, based on the results of this study it is suggested that the madrasah focus more on placing facilities for students, so that users of these facilities feel comfortable.